2019
DOI: 10.1525/elementa.341
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions from contrasting production regions within Alberta, Canada: Implications under incoming federal methane regulations

Abstract: Aggressive reductions of oil and gas sector methane, a potent greenhouse gas, have been proposed in Canada. Few large-scale measurement studies have been conducted to confirm a baseline. This study used a vehicle-based gas monitoring system to measure fugitive and vented gas emissions across Lloydminster (heavy oil), Peace River (heavy oil/bitumen), and Medicine Hat (conventional gas) develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 28 publications
1
45
0
Order By: Relevance
“…Using the same method as O'Connell et al (2019) to assess the distribution of site-level emissions rates in conventional and unconventional developments, we found that the emissions can be described using lognormal statistics, as previously observed by Zavala-Araiza et al (2015) and Zavala-Araiza et al (2018). As expected with lognormal distributions, a Lorenz curve shows that a small percent of sites is responsible for a large percentage of measured emissions ( figure 3).…”
Section: Interpretationssupporting
confidence: 70%
See 1 more Smart Citation
“…Using the same method as O'Connell et al (2019) to assess the distribution of site-level emissions rates in conventional and unconventional developments, we found that the emissions can be described using lognormal statistics, as previously observed by Zavala-Araiza et al (2015) and Zavala-Araiza et al (2018). As expected with lognormal distributions, a Lorenz curve shows that a small percent of sites is responsible for a large percentage of measured emissions ( figure 3).…”
Section: Interpretationssupporting
confidence: 70%
“…The survey data was analyzed to isolate CH 4 -rich plumes from the varying ambient atmospheric levels using ratios of super-ambient (or 'excess', denoted by 'e') CO 2 and CH 4 (eCO 2 :eCH 4 ). The gas ratio approach has been used previously by Atherton et al (2017), Williams et al (2018), andO'Connell et al (2019), though the most complete explanation is presented in Hurry et al (2016). Ambient atmospheric CO 2 and CH 4 vary spatiotemporally due to factors such as atmospheric stability, land-use types, and topography.…”
Section: Methodsmentioning
confidence: 99%
“…The average production normalized leakage rate for satellite pads and well sites is 0.21%, while that for super pads is 0.03%. These proportional loss rates are lower than many recent studies of methane emissions in Canada [6,8]. Figure 2(b) shows the absolute methane leakage volumes as a function of production for the same set of sites in figure 2(a).…”
Section: Resultsmentioning
confidence: 67%
“…Both ground-based and aerial-measurements in Alberta showed higher vented and total methane emissions compared to provincial regulatory estimates [5,6]. Similarly, mobile measurements using truck-mounted sensor systems in British Columbia and Alberta have consistently shown that a majority of the emissions are dominated by a small number of high-emitting sites, often identified as 'super-emitters' [5,7,8]. This is not unique to oil and gas activity in Canadameasurements of methane emissions across different shale basins in the US demonstrate evidence of superemitters, widespread underestimation compared to US EPA inventory, and significant spatial and temporal variability [9][10][11][12].…”
Section: Introductionmentioning
confidence: 92%
“…Deliberate venting of unwanted gas is a major source of emission in many oilfields. O'Connell et al () studied heavy oil wells around Lloydminster, Canada. Over 40% of sampled well pads were emitting detectable methane, and of these, 40% emitted above the venting threshold beyond which mitigation was required by Canadian federal regulations.…”
Section: Practical Emission Reduction and Removal—tractable Emissionsmentioning
confidence: 99%